1992
DOI: 10.2307/1940684
|View full text |Cite
|
Sign up to set email alerts
|

^(13)C and ^(15)N Enrichment Factors of Feathers of 11 Species of Adult Birds

Abstract: The use of stable isotopes of bioelements to analyze diets of animals in nature requires precise knowledge of any changes in the isotope ratios that take place after assimilation. Therefore, the influence of diet on the distribution of carbon and nitrogen isotopes in feathers of 11 species of birds on a constant diet was studied. The standard deviation in °13C and °15N in naturally obtained foods like fish during 6 yr was °1%. Factory—manufactured pellets generally gave lower deviations (0.2% for °13C and °0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 24 publications
6
96
0
Order By: Relevance
“…Mizutani et al (1990Mizutani et al ( , 1991 reported a ε feather-diet of 4‰ for stable carbon isotopes in free-ranging and captive cormorants and attributed the difference to the fractionation of 13 C as it is incorporated in the keratin of feathers. Mizutani et al (1992) extended this work to include other bird species and showed that ε feather-diet varied from 2.5 to 3.8‰, depending on species. Mizutani and Wada (1988), Mizutani et al (1990Mizutani et al ( , 1992 and Hobson and Clark (1992b) also observed significant differences in ε 13 C for regurgitant and feathers from free ranging and captive birds.…”
Section: Stable Isotopes and Tissue-diet Enrichment Factorsmentioning
confidence: 89%
See 3 more Smart Citations
“…Mizutani et al (1990Mizutani et al ( , 1991 reported a ε feather-diet of 4‰ for stable carbon isotopes in free-ranging and captive cormorants and attributed the difference to the fractionation of 13 C as it is incorporated in the keratin of feathers. Mizutani et al (1992) extended this work to include other bird species and showed that ε feather-diet varied from 2.5 to 3.8‰, depending on species. Mizutani and Wada (1988), Mizutani et al (1990Mizutani et al ( , 1992 and Hobson and Clark (1992b) also observed significant differences in ε 13 C for regurgitant and feathers from free ranging and captive birds.…”
Section: Stable Isotopes and Tissue-diet Enrichment Factorsmentioning
confidence: 89%
“…Mizutani et al (1992) extended this work to include other bird species and showed that ε feather-diet varied from 2.5 to 3.8‰, depending on species. Mizutani and Wada (1988), Mizutani et al (1990Mizutani et al ( , 1992 and Hobson and Clark (1992b) also observed significant differences in ε 13 C for regurgitant and feathers from free ranging and captive birds. Variability was attributed to a variety of factors including the relationship between the timing of feather growth and seasonality in the composition of potential prey and/or the lipid content of prey items (Bender et al 1981;Sullivan and Krueger 1981;Hobson and Clark 1992a).…”
Section: Stable Isotopes and Tissue-diet Enrichment Factorsmentioning
confidence: 89%
See 2 more Smart Citations
“…In general, consumer tissues are enriched in 15 N and 13 C relative to their diet by Ϸ3‰ and Ϸ1‰, respectively (26). However, controlled isotopic studies of diet and bird tissues show that these isotopic fractionations can vary significantly among tissue types and bird species (9,27,28). Although there are no controlled feeding studies of condors, recent work suggests that, as the protein content of diet rises, the diet-to-tissue fractionation increases for both carbon and nitrogen (28,29).…”
Section: Methodsmentioning
confidence: 99%